Modulation of sol mRNA expression by the long non-coding RNA Assolrna in Clostridium saccharoperbutylacetonicum affects solvent formation - Baur, Saskia Tabea; Poehlein, Anja; Renz, Niklas Jan; Hollitzer, Stefanie Karolina; Montoya Solano, José David; Schiel-Bengelsdorf, Bettina; Daniel, Rolf; Dürre, Peter (Frontiers in Genetics, 2022)
Solvents such as butanol are important platform chemicals and are often produced from petrochemical sources. Production of butanol and other compounds from renewable and sustainable resources can be achieved by solventogenic bacteria, such as the hyper-butanol producer Clostridium saccharoperbutylacetonicum. Its sol operon consists of the genes encoding butyraldehyde dehydrogenase, CoA transferase, and acetoacetate decarboxylase (bld, ctfA, ctfB, adc) and the gene products are involved in butanol and acetone formation. It is important to understand its regulation to further optimize the solvent production. In this study, a new long non-coding antisense transcript complementary to the complete sol operon, now called Assolrna, was identified by transcriptomic analysis and the regulatory mechanism of Assolrna was investigated. For this purpose, the promoter-exchange strain C. saccharoperbutylacetonicum ΔPasr::Pasr** was constructed. Additionally, Assolrna was expressed plasmid-based under control of the native Pasr promoter and the lactose-inducible PbgaL promoter in both the wild type and the promoter-exchange strain. Solvent formation was strongly decreased for all strains based on C. saccharoperbutylacetonicum ΔPasr::Pasr** and growth could not be restored by plasmid-based complementation of the exchanged promoter. Interestingly, very little sol mRNA expression was detected in the strain C. saccharoperbutylacetonicum ΔPasr::Pasr** lacking Assolrna expression. Butanol titers were further increased for the overexpression strain C. saccharoperbutylacetonicum [pMTL83151_asr_PbgaL] compared to the wild type. These results suggest that Assolrna has a positive effect on sol operon expression. Therefore, a possible stabilization mechanism of the sol mRNA by Assolrna under physiological concentrations is proposed.